3α,4α-Ep-oxy-5α-androstan-17β-yl acetate - Andrade, L. C. R. (2009)
The title compound, C(21)H(32)O(3), results from modifications of the A and D rings of the aromatase substrate androstenedione. Ring A adopts a conformation between 10β-sofa and 1α,10β half-chair. Rings B and C are in slightly flattened chair conformations. Ring D approaches a 13β-envelope conformation, probably due to the acet-oxy substituent, and shows a very short Csp(3)-Csp(3) bond next to the epoxide ring, which is characteristic of 3-4 epoxides. .